Analogy of Mycobacterium marinum Disease to Mycobacterium leprae Infection in Footpads of Mice - Ng, Herman (1973)
Because it appeared likely that the disease process that follows inoculation of footpads of mice with Mycobacterium marinum might serve as a useful model of mouse footpad infection with M. leprae for immunological studies. an attempt was made to establish an analogy between the two processes. As a second objective, the adequacy of measurements of mouse footpad thickness as an index of the total number of M. marinum and of the number of viable M. marinum was determined. The evolution of M. marinum disease in the footpads of BALB/c mice was observed, and the influences of mouse age and sex and of inoculum size were measured. Mice were challenged with M. marinum in one footpad at several intervals after inoculation of the contralateral hind footpad with the same organism. In all of these experiments, mouse footpad thickness was noted to parallel multiplication of M. marinum during the phase of increasing footpad swelling. Cessation of bacterial multiplication was noted to occur just before maximal swelling had been achieved, and was followed by rapid loss of viable M. marinum. The total number of organisms and mouse footpad thickness decreased only slowly and incompletely. Analogy between M. marinum disease and M. leprae infection of the mouse footpad was established by the self-limited nature of both processes, and by similar patterns of protection against homologous and heterologous challenge conferred by the two processes.